Comparison of Material Consumption, Experimental Protocols and Computation Time in DNA Computing - Rajaee, N.; Hong Ping, K.; Lit, A.; Salleh, D.N.S.A; Ng, L.Y (International Journal of Machine Learning and Computing, 2014)
One of the major constraints in DNA computation is the exponential increase in material consumption and computation time for larger computation size in DNA computing particularly in critical stages such as initial pool generation and extraction during gel electrophoresis. In DNA computation, both the hybridization-ligation method and parallel overlap assembly method can be utilized to generate the initial pool of all possible solutions. In this paper, we discuss and compare the implementation of N × N Boolean matrix multiplication via in vitro implementation between Hybridization-Ligation Method and Parallel Overlap Assembly Method to show that selection of tools and protocols affect the cost effectiveness of a computation in terms of the material consumption, protocol steps and execution time to compute. In general, the the parallel overlap assembly method performs better than hybridization-ligation method in terms of the three parameters mentioned. The calculations are based on approximation of unique sequence strands required for the computation and not actual calculations on the nmol concentration.